THE ANALYSIS OF ENERGY EMBODIED & GREENHOUSE GAS IN BUILDING CONSTRUCTION BY LIFE CYCLE ENERGY ANALYSIS METHOD - Sangsawang, Thibordin; Surachotivet, Teerachai (Srinakharinwirot University Journal of Sciences and Technology, 2023)
In this research, the embodied energy and greenhouse gas emissions of a multi-purpose building were studied. There are 3 parts; the embodied energy and greenhouse gas from building materials, transportation and energy consumption in construction. The results showed that the total embodied energy was 162,981,382.39 MJ, from building materials for 162,239,677.40 MJ, transportation for 643,934.89 MJ and energy consumption in construction for 97,770.10 MJ. The total greenhouse gas in this building was 14,511,534.50 kgCO2e, from building materials for 14,447,105.97 kgCO2e, transportation for 47,879.62 kgCO2e, and energy consumption in construction for 16,548.91 kgCO2e. The highest embodied energy and greenhouse gas emission were from steel and concrete. When the obtained values were averaged per area, found that for the embodied energy has 9.59 GJ/m2 and greenhouse gas has 853.62 kgCO2e/m2.